Pertussis Vaccine Candidate Based on Outer Membrane Vesicles Derived From Biofilm Culture - Carriquiriborde, Francisco; Martin Aispuro, Pablo; Ambrosis, Nicolás; Zurita, Eugenia; Bottero, Daniela; Gaillard, María Emilia; Castuma, Celina; Rudi, Erika; Lodeiro, Aníbal; Hozbor, Daniela F. (Frontiers in Immunology, 2021)
Outer membrane vesicles (OMV) derived from Bordetella pertussis—the etiologic agent of the resurgent disease called pertussis—are safe and effective in preventing bacterial colonization in the lungs of immunized mice. Vaccine formulations containing those OMV are capable of inducing a mixed Th1/Th2/Th17 profile, but even more interestingly, they may induce a tissue-resident memory immune response. This immune response is recommended for the new generation of pertussis-vaccines that must be developed to overcome the weaknesses of current commercial acellular vaccines (second-generation of pertussis vaccine). The third-generation of pertussis vaccine should also deal with infections caused by bacteria that currently circulate in the population and are phenotypically and genotypically different [in particular those deficient in the expression of pertactin antigen, PRN(-)] from those that circulated in the past. Here we evaluated the protective capacity of OMV derived from bacteria grown in biofilm, since it was observed that, by difference with older culture collection vaccine strains, circulating clinical B. pertussis isolates possess higher capacity for this lifestyle. Therefore, we performed studies with a clinical isolate with good biofilm-forming capacity. Biofilm lifestyle was confirmed by both scanning electron microscopy and proteomics. While scanning electron microscopy revealed typical biofilm structures in these cultures, BipA, fimbria, and other adhesins described as typical of the biofilm lifestyle were overexpressed in the biofilm culture in comparison with planktonic culture. OMV derived from biofilm (OMVbiof) or planktonic lifestyle (OMVplank) were used to formulate vaccines to compare their immunogenicity and protective capacities against infection with PRN(+) or PRN(-) B. pertussis clinical isolates. Using the mouse protection model, we detected that OMVbiof-vaccine was more immunogenic than OMVplank-vaccine in terms of both specific antibody titers and quality, since OMVbiof-vaccine induced antibodies with higher avidity. Moreover, when OMV were administered at suboptimal quantity for protection, OMVbiof-vaccine exhibited a significantly adequate and higher protective capacity against PRN(+) or PRN(-) than OMVplank-vaccine. Our findings indicate that the vaccine based on B. pertussis biofilm-derived OMV induces high protection also against pertactin-deficient strains, with a robust immune response.